Epichloë fungal endophyte interactions in perennial ryegrass (Lolium perenne L.) modified to accumulate foliar lipids for increased energy density - Kim A. Richardson; Anouck C. M. de Bonth; Zac Beechey-Gradwell; Suhas Kadam; Luke J. Cooney; Kelly A. Nelson; Ruth Cookson; Somrutai Winichayakul; Michele Reid; Philip Anderson; Tracey Crowther; Xiuying Zou; et al. (BMC Plant Biology, 2023)
Abstract Background Commercial cultivars of perennial ryegrass infected with selected Epichloë fungal endophytes are highly desirable in certain pastures as the resulting mutualistic association has the capacity to confer agronomic benefits (such as invertebrate pest deterrence) largely due to fungal produced secondary metabolites (e.g., alkaloids). In this study, we investigated T2 segregating populations derived from two independent transformation events expressing diacylglycerol acyltransferase (DGAT) and cysteine oleosin (CO) genes designed to increase foliar lipid and biomass accumulation. These populations were either infected with Epichloë festucae var. lolii strain AR1 or Epichloë sp. LpTG-3 strain AR37 to examine relationships between the introduced trait and the endophytic association. Here we report on experiments designed to investigate if expression of the DGAT + CO trait in foliar tissues of perennial ryegrass could negatively impact the grass-endophyte association and vice versa. Both endophyte and plant characters were measured under controlled environment and field conditions. Results Expected relative increases in total fatty acids of 17–58% accrued as a result of DGAT + CO expression with no significant difference between the endophyte-infected and non-infected progeny. Hyphal growth in association with DGAT + CO expression appeared normal when compared to control plants in a growth chamber. There was no significant difference in mycelial biomass for both strains AR1 and AR37, however, Epichloë-derived alkaloid concentrations were significantly lower on some occasions in the DGAT + CO plants compared to the corresponding null-segregant progenies, although these remained within the reported range for bioactivity. Conclusions These results suggest that the mutualistic association formed between perennial ryegrass and selected Epichloë strains does not influence expression of the host DGAT + CO technology, but that endophyte performance may be reduced under some circumstances. Further investigation will now be required to determine the preferred genetic backgrounds for introgression of the DGAT + CO trait in combination with selected endophyte strains, as grass host genetics is a major determinant to the success of the grass-endophyte association in this species.